Management of aortic valve disease during pregnancy: A review. Issue 5 (1st April 2019) - Maskell, Perry; Burgess, Mika; MacCarthy‐Ofosu, Beverly; Harky, Amer
Abstract: Cardiovascular disease represents a significant portion of pregnancy‐related complications and is associated with high rates of morbidity and mortality in this cohort. Cardiac valvulopathy, and aortic valve pathologies, in particular, pose a significant challenge to women who are pregnant and to the health care professionals who look after them. Depending on the type and severity of aortic valve pathology, pregnancy may exacerbate or accelerate the progression of valvulopathy sequelae because of the hemodynamic changes that occur from conception, throughout gestation, up to Labor and postpartum. Management of such patients ranges from basic conservative measures such as bed‐rest, extending to high‐risk emergency open heart surgery. This nonstructured review aims to highlight the current evidence available relating to the management of aortic valve disease in pregnancy, with a key focus on cases which requires intervention beyond that of medical therapy. In conclusion, the management of aortic valvulopathy in pregnancy is a challenging field with only a small amount of clinical experience and retrospective study supporting evidence‐based decisions in this field. A greater understanding of the most recent advances is recommended to support decision making in this specialist field of clinical medicine.